2007
DOI: 10.1196/annals.1422.037
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of the Soluble Tumor‐Associated Antigens CA19‐9, CA125, and CA15‐3 in Rheumatoid Arthritis

Abstract: Some tumor-associated antigens (TAAs) are expressed on inflammatory cells. We previously detected carcinoembryonic antigen (CEA; CD66) in the rheumatoid (RA) synovium. The production of CEA, CA19-9, CA125, and CA15.3, may be increased in patients with RA, scleroderma, lupus, and Sjögren's syndrome (SS). Some of these TAAs contain sialylated carbohydrate motifs and they are involved in tumor-associated cell adhesion and metastasis. We assessed levels of TAAs in the sera of RA patients and healthy subjects. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
(75 reference statements)
1
33
1
4
Order By: Relevance
“…In our findings, CEA levels have been found to be correlated with smoking history and serum RF levels however a correlation between disease activity score and CEA was not present. This finding is in accordance with another study also evaluating the level of serum tumor markers in RA patients in which disease activity was measured by DAS28 however in two other studies which also reported elevated CEA levels in RA patients, a correlation between RF and CEA levels were not found (11)(12)(13). Of interest there are a few studies in the literature that suggest CEA itself by binding to monocytes can trigger increased secretion of proinflammatuary cytokines such as tumor necrosis factor alfa, interleukin 1 beta and interleukin 6.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In our findings, CEA levels have been found to be correlated with smoking history and serum RF levels however a correlation between disease activity score and CEA was not present. This finding is in accordance with another study also evaluating the level of serum tumor markers in RA patients in which disease activity was measured by DAS28 however in two other studies which also reported elevated CEA levels in RA patients, a correlation between RF and CEA levels were not found (11)(12)(13). Of interest there are a few studies in the literature that suggest CEA itself by binding to monocytes can trigger increased secretion of proinflammatuary cytokines such as tumor necrosis factor alfa, interleukin 1 beta and interleukin 6.…”
Section: Resultssupporting
confidence: 79%
“…It is expressed on the cell surface and is responsible for cell adhesion to neighboring tissues (16 found that CA125 levels were significantly elevated in the patient group. In our study group CA 125 levels were found to be significantly higher in RA patients (11,12). Carbohydrate antigen 19-9 (CA 19-9) is a tumor associated oligosaccharide oncofetal antigen which is closely related to the sialylated Lewis blood group antigen (sLea).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that an increased ESR was associated with an increased CA 19-9 concentrations further supports this idea. Furthermore, CA 19-9 along with other tumor markers was recently proposed as an adhesion molecule in synovial inflammation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate antigen , also called sialylated Lewis antigen, is synthesized by normal human pancreatic and biliary ductal cells and by gastric, colon, endometrial, and salivary excretory epithelial tissues [7,8]. CA 19-9 is commonly used as a tumor marker for certain epithelial-type gastrointestinal cancers, particularly pancreatic.…”
Section: Www Journalsviamedicapl/ginekologia_polskamentioning
confidence: 99%